Endoscopic pathology of the larynx - Asha'ari, Zamzil Amin (2015)
Learning objectives of this workshop are to discuss the normal endoscopic anatomy of the pharynx and larynx, review some common abnormal findings on endoscopy and learning to do upper airway endoscopy in a target participants of the general practitioners.